FACTORS CAUSING WIFE WORKS AND IMPACTS - Jaenuri (AS-SALAM, 2015)
Life in Indonesian society is still very often encountered some problems within a family, one of which is a matter of working wives. Islamic religion does not forbid his wife to work even there are no rules on the prohibition of the wife works. In Sub Braja selebah wife works issue is still very much encountered almost every wife to work. participation and wife work outside the home is still an issue discussed from the first until now.This research is expected to provide insight for the development of science, especially in the areas of family law and can serve as a reference for similar studies in the future. This research is a field that is descriptive analysis. Data collection was conducted by interview, and documentation. And then analyzed using an inductive method of thinking.The results showed that factors cause the wife works are internal factors, namely: 1) factors and wife already worked before marriage 2) factors that arise when the wife wants to change the economic situation the family is still not very well be better 3) factors that arise when there collision problems in the family needs. External factors, namely: 1) factors that arise when their encouragement as well as feedback from neighbors and relatives 2) Demands age 3) gender equality would be related to the emancipation of women 4) educational factors. Of course with the state of the working wife have a good impact on the positive or negative effects. The positive impact of the wife works, namely: 1) the economy for the better 2) Quality of life improved 3) gender equality 4) establishment of family sakinah mawaddah wa Rahmah. Then the negative impact of the wife works, namely: 1) the divorce rate is increasing 2) juvenile delinquency 3) the loss of identity of the wife as mother 4) the number of pregnant mating phenomenon. Based on the results of research conducted in the District of Braja Selebah East Lampung district, which is based on data and interviews with respondents. That is a major factor in the wife works in the District Braja Selebah East Lampung district is a matter of economics.